-5q+1-5+1=

Simple and best practice solution for -5q+1-5+1= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5q+1-5+1= equation:


Simplifying
-5q + 1 + -5 + 1 = 0

Reorder the terms:
1 + -5 + 1 + -5q = 0

Combine like terms: 1 + -5 = -4
-4 + 1 + -5q = 0

Combine like terms: -4 + 1 = -3
-3 + -5q = 0

Solving
-3 + -5q = 0

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -5q = 0 + 3

Combine like terms: -3 + 3 = 0
0 + -5q = 0 + 3
-5q = 0 + 3

Combine like terms: 0 + 3 = 3
-5q = 3

Divide each side by '-5'.
q = -0.6

Simplifying
q = -0.6

See similar equations:

| 4x^3-42x^2+104x=0 | | a[x-(-2-3i)][x-(-2+3i)][x-(-5)][x-(-5)]=0 | | 2(3)-4y=8 | | 2(1)-4y=8 | | 3(x+14)= | | 4x^2-42x+104=0 | | 4(6)+12y=24 | | -72+4y=-4y | | 4(4)+12y=24 | | 6000=.5(x+2x)*2x | | 4x+3x=19 | | 4(2)+12y=24 | | xp^2-2yp+x=0 | | 5b^2+5b-30=0 | | 9x*9x= | | -10(5)-15y=45 | | -10(3)-15y=45 | | 3+5(n+6)=48 | | x-1/2=21/5 | | 3m+6n=85 | | -10(1)-15y=45 | | 10(1)-15y=45 | | 8x^2+10=490 | | (4+2x)(3+2x)=24 | | 3(x+76)= | | t^2-5t-(-6)=0 | | -2x-178=20 | | 5.6(8.3)= | | 15y-17y=12 | | f(x)=5x+0.5+3 | | v-1/3=3/4 | | 4x+3(3x-5)=3(x-1) |

Equations solver categories